Attenuated aroA Salmonella enterica serovar Typhimurium does not induce inflammatory response and early protection of gnotobiotic pigs against parental virulent LT2 strain - Trebichavsky, I; Splichalova, A; Rychlik, I; Hojna, H; Muneta, Y; Mori, Y; Splichal, I (Vaccine, 2006)
Cytokine and inflammatory response against virulent LT2 strain and its attenuated aroA deletion mutant of Salmonella enterica serovar Typhimurium were compared in gnotobiotic pigs. Contrary to the parental strain, the auxotrofic mutant did not induce IL-1beta, IL-18, TNF-alpha, and IFN-gamma in the ileum and plasma 24h after the infection, did not cause pathological changes in ileal epithelium and mesenteric lymph nodes or immunoreactivity of gp91 phox and peroxynitrite and was not immunostained for GroEL stress protein. The absence of induction of proinflammatory cytokines may be a reason why aroA mutant was unable to elicit any inflammatory response and protect pigs against challenge with virulent LT2 strain administered 24h later.
Keywords: gnotobiologické modely; prasata; Swine; Salmonella enterica; Inflammation; Germ-Free Life; virulence; vakcíny proti tyfu a paratyfu; cytokiny; Salmonella Vaccines; Typhoid-Paratyphoid Vaccines; imunohistochemie; Virulence; zánět; Animals; Genes, Bacterial; Immunohistochemistry; salmonelové vakcíny; zvířata; Vaccines, Attenuated; atenuované vakcíny; Cytokines; bakteriální geny